Empowering Karang Taruna as an Agent of Change in Improving Mental Health of Adolescents in Rural Communities - Jawiah; Khoirunnisa, Mirna; Jannah, Msy Miftahul; Prasetyo, Indah Ayu (International Journal Scientific and Professional, 2025)
Mental health issues among adolescents are becoming an increasingly significant issue, especially in rural areas such as Pangkalan Benteng Village. The lack of public understanding of this Issue and limited access to professional services are major challenges in efforts to improve the psychological well-being of adolescents. This community service program aims to empower Karang Taruna as agents of change in supporting adolescent mental health through training, mentoring, and educational activities. The implementation method includes identifying needs through surveys and FGDs, training Karang Taruna members on adolescent mental health and early intervention, establishing adolescent support groups, and implementing stress management workshops, awareness campaigns, and individual counselling sessions. The results of the activities showed a significant increase in the knowledge and concern of Karang Taruna members and adolescents about mental health, reduced stigma in the community, and the formation of a more supportive social environment. These findings indicate that empowering local communities such as Karang Taruna can be an effective strategy for addressing adolescent mental health issues and has the potential to be replicated in other villages in Indonesia.